Comparison of the free radical-scavenging activity of propolis from several regions of Argentina - Nieva Moreno, María Inés (2000)
Propolis is extensively used in Argentine folk medicine. Alcoholic extracts of propolis from different regions of Argentina were prepared. The extracts were analysed for the determination of total flavonoid content (from 13.3 to 42.6 mg/g of propolis) by using the aluminum nitrate method, UV spectrophotometry and thin layer chromatography. All of them contained high total flavonoid content. It was also observed that all samples of ethanolic extracts of propolis showed free radical-scavenging activity in terms of scavenging of the radical DPPH but the highest activities were found for samples from Tucuman and Santiago del Estero. In all cases with 20 μg/ml of soluble principles, the percentage of DPPH degradation was different (Banda Oeste: 67.5%; Veronica: 45%; Forres: 35%; Saenz Pena: 20% and Juan Jose Castelli: 55%). These results may justify their use as a source of natural antioxidants.